Does ischemia reperfusion affect fecundability in a rat model?. Issue 6 (June 2019) - Calis, Pinar; Erturk, Nergis; Bozdag, Gurkan
Abstract : Background: Adnexal torsion constitutes 2.7% of all gynecological emergencies. Because normal follicular growth has been demonstrated after examination of surgical specimens retrieved from oophorectomies, organ-sparing strategy has gained more popularity irrespective of the appearance of the ovary. However, the functionality of the remaining follicles has not been known. The aim of the study was to evaluate the effect of ischemia-reperfusion on fecundability in a rat model with adnexal torsion. Methods: A total of 30 female adult Wistar albino rats were assessed. In the first laparotomy, right ovaries were twisted for 8 (Group I, n = 10) or 24 (Group II, n = 10) hours. Second laparotomy was performed to untwist the torsion side and oophorectomy to the other side. In the control group (Group III, n = 10), left ovaries were removed and right ovaries were kept without any intervention. After 30 days from the last operation, female rats were mated for 10 days and euthanized 4 days later. Fecundability was calculated using beta-human chorionic gonadotropin (hCG) levels for detection of pregnancy rates. Results: The mean beta-hCG values in control, 8-hour, and 24-hour groups between pregnant rats were 19.8 ± 26.02, 11.7 ± 0.17, and 22.97 ± 11.87 mIU/mL, respectively. Whereas two out of 10 rats (20%) conceived in the 8-hour group, three out of 10 rats (30%) got pregnant in the 24-hour group. In total, whereas five out of the 20 rats got pregnant in the experimental groups, in the control group, seven out of 10 subjects conceived (25% vs 70 %, p = 0.018). Conclusion: Although there was a statistical difference between experimental and control groups, statistical significance was not reached among 8-hour and 24-hour torsion subgroups. In this context, patients with torsion but treated with detorsion should be further investigated for their fecundability potency and be informed accordingly.